2016
DOI: 10.1007/s11748-016-0679-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis for prediction of early and long-term survival in patients receiving intra-aortic balloon pumping after cardiac surgery

Abstract: BackgroundPatients requiring an intra-aortic balloon pump (IABP) after cardiac surgery are critically ill and need a prolonged ICU stay. Considering limited health care resources, the early identification of patients with an extremely poor prognosis is important as a solid base for the decision whether further aggressive continuation or cessation of the therapy is recommendable.MethodsFrom 2001 to 2007, 552 patients with low-output syndrome after open-heart surgery and IABP implantation in OR or within 24 h th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…These incidents are not surprising because the number of older patients is growing, and they have more coexisting diseases (such as chronic kidney injury, peripheral vascular disease and others), which affect outcomes of critically ill patients, particularly cardiac surgery patients (independent of the need for IABP-support). ( 12 , 13 ) More specifically, a study in 2016 with 522 patients found that age above 70 years was an independent risk factor for mortality within 30 days. ( 12 ) In addition, in 2015, another working group of 572 patients concluded that patients older than 65 years undergoing IABP support had higher in-hospital mortality rates in comparison to younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These incidents are not surprising because the number of older patients is growing, and they have more coexisting diseases (such as chronic kidney injury, peripheral vascular disease and others), which affect outcomes of critically ill patients, particularly cardiac surgery patients (independent of the need for IABP-support). ( 12 , 13 ) More specifically, a study in 2016 with 522 patients found that age above 70 years was an independent risk factor for mortality within 30 days. ( 12 ) In addition, in 2015, another working group of 572 patients concluded that patients older than 65 years undergoing IABP support had higher in-hospital mortality rates in comparison to younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…( 12 , 13 ) More specifically, a study in 2016 with 522 patients found that age above 70 years was an independent risk factor for mortality within 30 days. ( 12 ) In addition, in 2015, another working group of 572 patients concluded that patients older than 65 years undergoing IABP support had higher in-hospital mortality rates in comparison to younger patients. ( 14 ) In the same direction, two studies in 2015 and 2016 included advanced age as one of the most important predictors of in-hospital mortality and adverse long term prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients and those with a higher degree of comorbidities are currently referred for cardiac surgery [ 4 ], and, even if such patients may benefit from cardiac surgery, they are at increased risk for perioperative complications that result in high morbidity and mortality [ 5 ]. Patients with a severely depressed left ventricular ejection fraction (LVEF < 35%) are particularly at increased risk of developing postoperative low cardiac output syndrome (LCOS) [ 6 ], which in turn is associated with higher mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the vast majority reference publications of in-hospital (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)) and short-term (2-6 months) outcomes of CABG with IABP support (17,18), the long-term outcomes (mainly up to 15 years) are limited to as few as 9 series, which are mostly presented by analysis of the either long-term survival, or mortality. The analysis was conducted without differentiation between isolated and combined CABG with correction of MI (myocardial infarction) mechanical complications/valvular prosthesis; elective/urgent surgery (18)(19)(20)(21)(22)(23). The long-term outcomes in isolated on-pump/off-pump CABG were analyzed in three series (1,4,20); the outcomes of isolated and combined CABG -in 6 series (6,7,10,11,18,19).…”
Section: Introductionmentioning
confidence: 99%